Implikasi Pembelajaran Sains Terpadu (Integrated Science Instruction) di SMP - Mujakir Yasin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
The instruction of Integrated Science at Junior High School considers with the use of Inquiry Approach. The students are provided with the daily reality occurs in their life. The Integrated Science at Junior High School has some features covering the developing ability in questioning, searching the questions, understanding the questions, and completing the questions on â€œwhatâ€, â€œwhyâ€, and â€œhowâ€ about the natural symptom as well as its characteristics systematically that to be applied in the environment and the technology. Such understanding of that integrated should be balanced with the studentsâ€™ psychology in which they are led to the content, so the process and the psychomotor are more urgent but the cognitive side is not to be ignored.